Pembentukan Portofolio Optimal Menggunakan Single Index Model Pada Saham IDX Value 30 - Ninin Non Ayu Salmah; Yasir Arafat; Tri Darmawati; Reina Damayanti (Ekonomis: Journal of Economics and Business, 2023)
This study aims to determine the stocks that can be included in the optimal portfolio of IDX Value30, the proportion of funds invested in each IDX Value30 stock, the return and risk of the optimal portfolio of IDX Value30 shares using the single index model and to determine whether there are differences average expected return and average risk between IDX Value30 stocks included in the portfolio and IDX Value30 stocks not included in the portfolio. This type of research is descriptive qualitative research. The population is shares of companies that are included in the IDX Value30 list for the announcement period from 2019 to 2022. The sampel is determined using nonprobability sampling with a purpose sampling method. Data analysis techniques are descriptive analysis and inferential statistical analysis. The research result obtained 2 optimal portfolio forming stocks with a single index model, namely ADRO shares with a proportion in the portfolio of 26.93% and UNTR of 73.07% and a portfolio return of 2,45% with a portfolio risk 1.41%. There is a difference in the average expected return between IDX Value30 stocks that are included in the portfolio and IDX Value30 stocks that are not included in the portfolio and there is no difference in the average risk between IDX Value30 stocks that are included in the portfolio and IDX Value30 stocks that are not included in the portfolio.